2020
DOI: 10.5897/ajpac2019.0815
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiling of the Hexane fraction of Crassocephalum crepidioides Benth S. Moore leaves by GC-MS

Abstract: Crassocephalum crepidioides is an edible plant which is also used in the ethnomedical treatment of stomach ulcer, indigestion, wounds, boils and burns in Africa and some other parts of the world. This study aims at identifying and characterizing the bioactive compounds present in C. crepidioides hexane fraction which may be responsible for the ethnomedicinal uses and reported activities of the plant. The crude extract from the powdered leaves of C. crepidioides was obtained with 70% methanol, followed by solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The hexane fraction of C. crepidioides was previously characterized by GC-MS, and it identified the presence of n-hexadecanoic acid, hexadecanoic methyl ester, and alpha-linolenic acid with lipid-lowering effects. [33] Histopathological analysis of the pancreatic tissues of the experimental rats revealed that the islet of Langerhans of the STZ-induced rats developed degenerative changes that led to shrinkage, which decreased the number of islet cells compared to the normal control rats. Similar to Li et al, [49] who performed a morphometric analysis of the islet endocrine cells in STZ-induced type I diabetes, reported that the area of the islet cells decreased by up to 35%, the number of insulin-positive beta cells gradually decreased, and the number of alpha cells increased by 2-3 times per islet area.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The hexane fraction of C. crepidioides was previously characterized by GC-MS, and it identified the presence of n-hexadecanoic acid, hexadecanoic methyl ester, and alpha-linolenic acid with lipid-lowering effects. [33] Histopathological analysis of the pancreatic tissues of the experimental rats revealed that the islet of Langerhans of the STZ-induced rats developed degenerative changes that led to shrinkage, which decreased the number of islet cells compared to the normal control rats. Similar to Li et al, [49] who performed a morphometric analysis of the islet endocrine cells in STZ-induced type I diabetes, reported that the area of the islet cells decreased by up to 35%, the number of insulin-positive beta cells gradually decreased, and the number of alpha cells increased by 2-3 times per islet area.…”
Section: Discussionmentioning
confidence: 98%
“…The hexane fraction was analyzed for the phytochemical constituents using Gas Chromatography-Mass Spectrometry (GC-MS) and has been reported. [33]…”
Section: Preparation Of Extracts and Phytochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation